PENGARUH FRAUD DIAMOND TERHADAP KECURANGAN AKADEMIK DENGAN MOTIVASI BELAJAR SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA MAHASISWA S1 AKUNTANSI DI UNIVERSITAS PATTIMURA AMBON) - Leunufna, Felix Dance Laurens; Pattinaja, Elna; Kriswantini, Dwi (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2023)
Research is a type of descriptive research, which describes the characteristics of a population or a phenomenon that is the object of research. The population in this study were undergraduate students in the Accounting study program, Faculty of Economics and Business, Pattimura University, Ambon. The author took samples using the purposive sampling method. The number of samples in this study was 400 respondents. Students who are still active are categorized, namely students from the 2019 and 2020 classes. The reason the researcher decided to take samples from students from the 2019 and 2020 classes was because these students had taken and were currently taking courses in Accounting Information Systems 1, Accounting Information Systems 2, Auditing 1 and Auditing 2, and because these students already knew about the fraud triangle theory, in where currently a new theory has developed, namely the fraud diamond theory. The data used in this research was collected via an online questionnaire. Researchers used multiple linear regression analysis and Moderated Regression Analysis (MRA) as data analysis techniques. The statistical tool used by the author in this research is SPSS 17. The results of this research show the influence of the variables in the fraud diamond on academic cheating and the influence of the learning motivation variable in moderating the variables in the fraud diamond on academic cheating, with data obtained from 206 respondents. 1) Pressure has a significant effect on academic cheating, while opportunity, rationalization and ability have no significant effect on academic cheating, 2) learning motivation can significantly moderate pressure and opportunity on academic cheating, while rationalization and ability cannot be significantly moderated by learning motivation on academic cheating